The pragmatic competence of Finnish and Japanese learners of English : a comparative study with emphasis on the effect of cultural differences - Laaksonen, Miro (My University, 2019)
This thesis studies the pragmatic competence of Finnish and Japanese English learners. The pragmatic competence of the learners in the two countries were compared for the implications the differences might have for teaching of pragmatic competence. In addition, the thesis investigated the effect cultural distance might have on pragmatic competence, as Japan and Finland have different cultural distances to the target language country of Great Britain. The subjects of this study consisted of two groups, a group of 64 first year upper secondary school English learners from Finland and a group of 69 first year high school English learners from Japan. The pragmatic competence of these two groups of learners was assessed with a multiple choice test of pragmatic competence which was adapted from two pre-existing test batteries. The test scores and the answers of the two groups were contrasted with each other in order to establish differences between the two groups of learners. The correlation of the scores in contrast to the countries’ cultural distance from Great Britain was also assessed in order to investigate the effect cultural distance might have on the pragmatic competence. The study found that there were significant differences between the pragmatic competence of Finnish and Japanese learners, with Finnish learners achieving significantly higher scores in the test of pragmatic competence. This was true with both pragmalinguistic and sociopragmatic competence. The study also found that cultural distance correlated negatively with pragmatic competence, meaning that higher cultural distance to the target language country negatively affected pragmatic competence. The results appear to have implications for teaching of pragmatic competence as Japanese students achieved significantly lower scores for pragmatic competence and previous studies have established that classroom instruction can be effective for teaching of pragmatic competence. Future studies could investigate what kind of differences in the curricula or teaching methods between Finland and Japan could have caused these differences. In addition, as cultural distance appears to have a role in the development of pragmatic competence, assessing how large role it has in contrast to other possible explaining factors could be done more accurately in a future study.